Chronic uphill and downhill exercise protocols do not lead to sarcomerogenesis in mouse skeletal muscle. (2nd January 2020) - Morais, Gustavo Paroschi; da Rocha, Alisson L.; Neave, Louise M.; de A. Lucas, Guilherme; Leonard, Timothy R.; Carvalho, Andrea; da Silva, Adelino Sanchez R.; Herzog, Walter
Abstract: It has been suggested that eccentric contraction (EC) is associated with increases in serially arranged sarcomeres (sarcomerogenesis), while concentric contraction (CC) has been associated with serial sarcomeres decrease. Sarcomerogenesis following EC is thought to be a protective muscle adaptation, preventing muscle injury in future eccentric exercise bouts (repeated bout effect). However, the mechanisms underlying sarcomerogenesis in EC remain unknown, and the sarcomerogenic responses observed in response to EC and CC are contradictory. We measured sarcomere length, sarcomere length uniformity, serial sarcomere number, and fascicle length in gastrocnemius medialis, tibialis anterior, vastus medialis and vastus lateralis in sedentary (SED) mice, and in mice following protocols of moderate uphill (TRU) and downhill (TRD) training and uphill (OTU) and downhill (OTD) overtraining. We found pain sensitivity after the first bout of EC exercise on TRD and OTD followed by a normalized sensory response after four weeks of training, indicating a repeated bout effect. However, these findings were not associated with sarcomerogenesis, as serial sarcomere numbers did not increase in TRD and OTD skeletal muscle samples compared to controls (SED). However, we found a decrease in serial sarcomere number in VL and TA in OTU group mice, which was associated with a decrease in fascicle length and no change of sarcomere length at the tested joint configuration. We conclude that excessive concentric muscle contraction (OTU group mice), leads to a decrease in serial sarcomere number, while moderate or excessive eccentric training, did not result in sarcomerogenesis, as reported in the literature.